Development of active bilayer packaging films incorporated with mangosteen pericarp extract and their application in packaging of palm oil - Brahim, Nabilah (2018)
Lipid oxidation in foods is one of the main causes of food spoilage. The oxidation occurrence can be slowed down or delayed by the incorporation of antioxidants into foods or in the packaging system as active packaging. The application of active packaging system has been recently approached in controlling the process of lipid oxidation. In the present study, an active bilayer film for food packaging comprises of a synthetic and bio-based polymer was developed. A natural antioxidant obtained from mangosteen pericarps extract (MPE) was the source for the antioxidant compounds in this active bilayer film. A study on single active bio-based film was conducted beforehand to determine the best carrier agent for antioxidant compounds to be incorporated in the packaging film. From the three carriers (fish gelatin, soy protein isolate and corn starch), soy protein isolate (SPI) outperformed the others due to the structure of SPI that can allow more antioxidant molecules to be attached to it. Then, the active SPI film was laminated on polyethylene (PE) film to develop an active bilayer film with an antioxidant property. The antioxidant activity was evaluated during storage for nine weeks at 25 and 40°C. The antioxidant activity of the film decreased significantly (P ≤ 0.05) after nine weeks of storage and even decreased faster at high storage temperature. Generally, storage and temperature do affect the antioxidant activity of the bilayer film as the active compounds were slowly released. The gradual released of antioxidants in MPE provide a longer time for usage in food packaging system. Hence, the oxidative stability of palm oil packaged in the active bilayer film was determined. The packaged palm oil was stored for 35 days at 25°C and at high high temperature, 40°C. The oxidative stability of palm oil was greater in the active bilayer film compared to the PE film alone (control). The oxidation measurements of palm oil increased slowly in the active bilayer film rather than faster increased in PE film. Therefore, MPE is capable of delaying the development of rancidity in food due to oxidation and confirmed the ability of active packaging to increase the oxidative stability of lipid foods.